Analisis Program SIAPP KAKA dalam Mempercepat Proses Pembuatan NIB (Nomor Induk Berusaha) (Studi Kasus Kelurahan Mayangan) - Verto Septiandika; Andhi Nur Rahmadi; Siti Nur Fadilah (Lembaga Yasin AlSys, 2025)
Business legality is a crucial factor for Micro, Small, and Medium Enterprises (MSMEs) in gaining access to various business development facilities. However, bureaucratic complexity and low public awareness regarding business legality remain major obstacles in obtaining a Business Identification Number (Nomor Induk Berusaha, NIB). This study aims to analyze the implementation of the SIAPP KAKA Program (Aksi Andalan Pendampingan Pelayanan Perizinan di Kecamatan dan Kelurahan) in accelerating the NIB issuance process in Mayangan Village, Probolinggo City. A descriptive qualitative method was employed, with data collected through observation, in-depth interviews, and documentation. The findings reveal that the SIAPP KAKA Program has successfully expedited licensing services through a proactive (jemput bola) approach, resulting in greater time and cost efficiency, and improved coordination between the subdistrict office and the Investment and One-Stop Integrated Service Agency (DPMPTSP). Nevertheless, the program's implementation still faces challenges, including limited human resources and infrastructure. Overall, the program has made a positive contribution to enhancing public service delivery and business legality, and it holds potential as an innovative model for locally based licensing services.